Psychological Complications at 3 Months Following Stroke: Prevalence and Correlates Among Stroke Survivors in Lebanon - Khazaal, Walaa; Taliani, Maram; Boutros, Celina; Abou-Abbas, Linda; Hosseini, Hassan; Salameh, Pascale; Sadier, Najwane Said (Frontiers in Psychology, 2021)
Introduction: Stroke continues to be a common and debilitating medical condition which has a significant effect on public health as the second primary source of mortality and the third major root of disability worldwide. A wide range of complications affecting the survivor's life and interfering with the recovery process usually follows stroke; anxiety and depression are considered one of the major complications post-stroke. This study sought to investigate the short-term psychological consequences of stroke among Lebanese survivors and to identify their correlates. Methods: This study is a prospective observational epidemiological study. 143 stroke patients admitted to hospitals in Mount Lebanon and Beirut between February and May 2018.were included in this study. Assessments of complications were carried out at 3 months post-stroke by completing a 30-min face-to-face interview questionnaire. The survey included the socio-demographic -characteristics of the patients, their lifestyle, health indicators, the severity of stroke, and the post-stroke consequences disturbing their quality of life. Results: Complications were recorded for 117 stroke survivors (mean age, 72.46 years; 60.7% male). The analysis of results 3 months post stroke showed that 29 survivors suffered from neuropathic pain (24.8%), 110 (94%) suffered from fatigue, and 81 (69.2%) from cognitive impairment. High rates of anxiety (51.3%), and depression (76.1%) were recorded as well. Multivariate logistic regression confirmed that there is a significant association between depression and the following variables: anxiety (OR = 4.814, p-value = 0.017), pain (OR = 6.868, p-value = 0.002), and physical activity, which acts as a protective factor against depression (OR = 0.261; p-value = 0.029). However, the results of the multivariate logistic regression analysis for anxiety indicated that immobility-related complications increase the risk of anxiety by 8.457 in sedentary duration longer than 12 h (ORa = 8.457, p-value = 0.01). Furthermore, patients with neuropathic pain (24.8%) are 3.858 times more likely to have anxiety compared to patients without neuropathic pain (ORa = 3.858, p-value = 0.019). Conclusion: Using a patient-centered structure more interventions should take place to evaluate stroke survivors' outcomes, and organize rehabilitation services that deal with stroke consequences, particularly high anxiety and depression levels, which are prevalent and persistent among the Lebanese stroke survivors.